Evaluation of the Welch Allen Microtympanometer compared to conventional examination methods : the effect of general anaesthesia on microtympanograms and middle ear effusions : the use of tympanometry in pre-school audiological screening programme - Black, John Henry (Division of Otorhinolaryngology, 2017)
1) Test the accuracy of the Welch Allyn Microtympanometer against standard tympanometry. 2) Correlate preoperative clinical findings with: • Microtympanometry • Standard tympanometry 3) Assess influence of induction by gas anaesthesia on: • Post-induction microtympanometry • Intraoperative myringotomy findings 4) Assess the practicality of using the Welch Allyn Microtympanometer as a screening tool in Pre-School audiological testing.